Analysing implied volatility smirk to predict the US stock market crash during the global financial crisis - Tanvir Bhuiyan; Ariful Hoque; Thi Le (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This study analyses the presence of implied volatility smirk (IVS) and its predictability of the US stock market crash during the Global Financial Crisis (GFC) through the in-sample and out-of-sample tests. The in-sample investigation was conducted for 18 cases (cases 1–18) to confirm the development of IVS during GFC (2007–2009). It also examined another 18 cases (cases 19–36) to ensure the absence of the IVS in the post-GFC period (2010–2011). Finally, an out-of-sample test analysed 63 cases (cases 37–99) to assess the predictability of IVS for the stock market crash during the GFC. The study reveals several critical findings. The in-sample test results show the negative return from simultaneous trading of out-of-the-money put options (OTMP) and at-the-money call options (ATMC) due to out-of-the-money put options implied volatility (OTMPIV) is higher than at-the-money call options implied volatility (ATMCIV) for all 18 cases (cases 1–18), confirming the development of IVS during GFC. However, findings of the in-sample test for cases 19–36 reveal the positive return from simultaneous trading of OTMP and ATMC because of the lower value of OTMPIV compared to ATMCIV, ensuring no occurrence of IVS in the post-GFC period. Finally, only 13 out of 63 cases (from cases 37–99) under the out-of-sample test show the IVS can forecast negative returns in an abnormal stock market. Further, the predictability of IVS for the US stock market crash depends on the maturity of options, forecast horizon, and options trading period